GDR Literature in German Curricula and Textbooks Exploring the Legacy of GDR Authors, 1985-2015 - Steding, Elizabeth Priester (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2023)
This book analyzes the changing portrayal of GDR literature in German Gymnasium textbooks 1985-2015. Addressing the need for textbook research to broaden its focus from GDR history to GDR literature, the author presents case studies of well-known GDR authors (Bertolt Brecht, Johannes R. Becher, Anna Seghers, Wolf Biermann, and Christa Wolf), each examining a particular aspect of the societal discourse about GDR literature and the tension between (literary) text and (historical) context. Taken together, the case studies reveal the frequently underestimated power of ideology in literature textbooks. They also show how attempts to package these authors into simplified categories ultimately reveal the profound complexities of the GDR literary legacy. By examining the clear tension between literature and politics in textbooks and curricula, the author demonstrates how ideological messages are transmitted in all textbooks, as well as the importance of attending to overt and covert ideology. .
Chapter 1. Introduction -- Chapter 2. What's Behind Textbooks? Federal and State Documents -- Chapter 3. Everybody loves Brecht -- Chapter 4. Anna Seghers and Johannes R. Becher as GDR Authors -- Chapter 5. Reading (About) Wolf Biermann -- Chapter 6. Everybody's Darling? Christa Wolf (and Günter Grass) -- Chapter 7. Conclusion.
Keywords: Education -- Curricula; Teaching; Literature -- History and criticism; Literature, Modern -- 20th century; Literature, Modern -- 21st century; Europe, Central -- History; Education -- Philosophy; Curriculum Studies; Didactics and Teaching Methodology; Literary History; Contemporary Literature; History of Germany and Central Europe; Educational Philosophy